ANALISIS DISTRIBUSI DAN MARGIN PEMASARAN IKAN CAKALANG DI KEDONGANAN, KABUPATEN BADUNG - Ekayani, Ni Luh Novi; Satriawan, I Ketut; Mulyani, Sri (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 3 (2019): SeptemberDO - 10.24843/JRMA.2019.v07.i03.p05, 2019)
This study aims to determine the marketing distribution line of cakalang fish from fishermen in Kedonganan to the end consumers and calculate the marketing margins obtained in each distribution channel. This research was conducted in July-September 2018. This study uses a survey method that uses sampling techniques namely purposive and snowball sampling. There are 4 distribution lines of cakalang fish in Kedonganan, Badung Regency from fishermen in Kedonganan to the final consumers, namely Line I ( Fisherman ® Collectors ® Market Traders ® Consumer ), Line II ( Fisherman ® Collectors ® Market Traders ® Motorcycle Traders ® Consumer ), Line III ( Fisherman ® Market Traders ® Consumer ), Line IV ( Fisherman ® Market Traders ® Motorcycle Traders ® Shopkeeper ® Consumer ) . Market and profit margins on each distribution line of cakalang fish in Kedonganan, Badung Regency from fishermen in Kedonganan to end consumers, namely on line I the marketing margin is Rp. 5.833,33/kg and the profit margin is  Rp. 3.226,68/kg, line II marketing margin of Rp. 8.175,00/kg and profit margin of Rp. 3.503,42/kg, line III l marketing margin of Rp. 5.500,00/kg and profit margin of Rp. 4.095,74/kg, line IV marketing margin of Rp. 12.500,00/kg and the profit margin is Rp. 6.853,39/kg. Keywords: cakalang fish, distribution lines, marketing margins, profit margin